PENGAKUAN PARA PIHAK SEBAGAI PERTIMBANGAN HAKIM DALAM MEMUTUS PERCERAIAN DI PEGADILAN AGAMA SAMARINDA (Studi Kasus Di Pengadilan Agama Samarinda ) - Arbain Arbain (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTThe existence of Religious Courts under Act No. 7 of 1989, as amended by Act No. 3 of 2006 one of the courts in Indonesia, in addition to the District Court, the Military Court and the Administrative Court as stipulated in Law No. 14 of 1970 on the Main Principles of Judicial Power, which has been revised in Law No. 35 of 1999 and subsequently converted into Law No. 48 of 2009 on Judicial Power.One form of the examination process in the civil procedural law of evidence used as a tool to convince the judge the truth of the proposition or the reasons set forth in the dispute. Some problems can be formulated in this research is how the inspection procedure and whether the recognition of a divorce case can be accepted as proof that stand alone in a divorce case in the Religious.Preparation of this paper by using the library (library research) literature that the basic material in the form of expert opinions and legal provisions of law that there is a link with the issues mentioned above as well as conduct research with interviews and observations in the Religious Court Samarinda.The results of the study authors get is a divorce case examination procedure in Samarinda Religious Courts in accordance with applicable law. Recognition in the case of divorce cases in the Religious Court can not be used as evidence but must be corroborated by other evidence.The conclusion of this study is the author of the examination procedure in Samarinda Religion divorce cases in accordance with applicable law and recognition can not be used as evidence in the trial. Advice the author gives is that the admission as evidence can be applied also to avoid multiple interpretations that need to be regulated in the law in Indonesia.Keywords: Recognition of Marriage Act Law 1 1974, recognition as one type of evidence